Advanced Integrated Mouse YAC Map Including BAC Framework - Schalkwyk, Leonard C.; Cusack, Brian; Dunkel, Ilona; Hopp, Martina; Kramer, Markus; Palczewski, Stefanie; Piefke, Jutta; Scheel, Sabine; Weiher, Michael; Wenske, Gunther; Lehrach, Hans; Himmelbauer, Heinz (Genome Research, 2001)
Functional characterization of the mouse genome requires the availability of a comprehensive physical map to obtain molecular access to chromosomal regions of interest. Positional cloning remains a crucial way of linking phenotype with particular genes. A key step and frequent stumbling block in positional cloning is making a contig of a genetically defined candidate region. The most efficient first step is isolating YAC (Yeast Artificial Chromosome) clones. A robust, detailed YAC contig map is thus an important tool. Employing Interspersed Repetitive Sequence (IRS)-PCR genomics, we have generated an advanced second-generation YAC contig map of the mouse genome that doubles both the depth of clones and the density of markers available. In addition to the primarily YAC-based map, we located 1942 BAC (Bacterial Artificial Chromosome) clones. This allows us to present for the first time a dense framework of BACs spanning the genome of the mouse, which, for instance, can serve as a nucleus for genomic sequencing. Four large-insert mouse YAC libraries from three different strains are included in our data, and our analysis incorporates the data of Hunter et al. and Nusbaum et al. There is a total of 20,205 markers on the final map, 12,033 from our own data, and a total of 56,093 YACs, of which 44,401 are positive for more than one marker.[The sequence data described in this paper have been submitted to the GenBank data library under accession nos. BH174059–BH175013.]